Need Analysis of Lesson Planning to Teach Education Value of Sulawesi Ethnic Dance Teaching in Primary School - Wahira, Wahira (Harmonia: Journal of Arts Research and Education, 2016)
This study aims to find out need analysis of lesson planning to teach education value of Sulawesi ethnic dance which comprises learning material, teaching method and learning model, learning media, as well as an assessment instrument. A method implemented in this study was research and development (R&D) with three main stages, namely, preliminary study, developmental research, and evaluation. This study, however, will only implement the first stage of study which is the preliminary study. This is implemented to perform need and content analysis. Results showed that need of lesson planning to teach education value of Sulawesi ethnic dance comprises learning material, teaching method and learning model, learning media, as well as an assessment instrument belongs to the category of â€œvery importantâ€ and that the planning is needed by teachers in teaching Sulawesi ethnic dance value for students in primary school.